2011
DOI: 10.1590/s0102-09352011000400020
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros genéticos de escore visual do umbigo em bovinos da raça Nelore

Abstract: Foram utilizados 128.700, 44.227, 90.383, 47.506, 42.619, 45.057, 17.666 e 27.181 dados, respectivamente, de peso à desmama (PD), peso ao sobreano (PS), escore de umbigo à desmama (UD), escore de umbigo à desmama de macho (UDM), escore de umbigo à desmama de fêmea (UDF), escore de umbigo ao sobreano (US), escore de umbigo ao sobreano de macho (USM) e escore de umbigo ao sobreano de fêmea (USF) com o objetivo de estimar parâmetros genéticos de escore visual do umbigo e as respectivas correlações genéticas com a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…Navel heritability was 0.36, which is higher than that observed by Koury and Bignardi et al (2011). These studies were carried out on-farm and not under more controlled conditions of a central performance test with standardization of age and type.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Navel heritability was 0.36, which is higher than that observed by Koury and Bignardi et al (2011). These studies were carried out on-farm and not under more controlled conditions of a central performance test with standardization of age and type.…”
Section: Resultsmentioning
confidence: 68%
“…The navel is important for Zebu-type cattle. Bignardi et al (2011) stated that bulls with long foreskin or a tendency to expose the foreskin membrane are subject to inflammation, injury, and trauma. For the navel (Table 1), the average (3.23) was slightly higher than that found by Koury Filho et al (2003) who found 3.09 for Nelore.…”
Section: Resultsmentioning
confidence: 99%
“…This difficulty may be related to the number of parameters to be estimated by the functions, because in models with less parameterized functions such as LEG3 and WIL functions, no genetic correlation negative estimates were observed (Tables 8 and 11). In studies by Brotherstone, White, and Meyer (2000), Pereira et al (2010) and Bignardi et al (2011) negative estimates of genetic correlations between yields made at the beginning and end of lactation were also reported. Difficulties of adjustment of genetic and permanent environmental correlations for LEG5 also were verified of Dornelles et al (2016).…”
Section: Resultsmentioning
confidence: 94%
“…The study herein also estimated the heritability of SA and VT to be 0.12 and 0.16 respectively. Finally, sheath score was estimated to have a high heritability of 0.49, this is higher than previous estimates, which ranged from 0.18 to 0.38 (Bignardi et al 2011;Gordo et al 2012;Corbet et al 2013). This higher heritability is likely to be due to difference in Sheath between parent breeds.…”
Section: Heritability Of Male Female and Composition Traitsmentioning
confidence: 65%